Kewenangan Bagi Jaksa untuk Melakukan Penyidikan dalam Perkara Tindak Pidana Korupsi - Ismaidar Ismaidar; Bonar Yudhistira (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
In handling corruption crimes, prosecutors can act as investigators and also as public prosecutors, so their role in eradicating corruption crimes by means of a penalty is very dominant, by means of a penalty meaning eradication of criminal acts by using criminal law in handling them. Until now, there are still many corruption cases whose investigations are carried out by prosecutors. However, there are different opinions regarding whether prosecutors have the actual authority as investigators of corruption crimes. This issue has emerged long before the Corruption Eradication Commission was established, especially after the Criminal Procedure Code was enacted, and the debate continues to this day.